The language situation in some Arab States: Arabization of the education system and its terms. - Mustafayeva., A. A.; Kydyrbayev., K. A. (Journal of Oriental Studies, 2016)
Arabization of the education system and its terms is a developing process depends on several factors, including political, economic and linguistic. Arabization of education (syllabus, teaching disciplines) and the terms in it plays a role in a language policy and situation, held every Arab state. The lack of Arabization unification, including terms requires consideration of each country separately. In this paperan attempt is made to consider the Arabization after the European colonialism.